(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluation of treatment adherence and identification of some factors related to treatment adherence of parents of Kawasaki patients with coronary artery lesions treated as outpatients at the National Children’s Hospital, 2021. Methods: Design of a cross-sectional descriptive study with 155 parents of pediatric Kawasaki patients with coronary lesions at Cardiology Center from March 2021 to August 2021. Results: The medication compliance rate of parents of Kawasaki children was 76.1%, with an average score of 6.83± 1.07 points. The group using antiplatelet drugs alone achieved medication compliance of 64.6% (62/96) and the rate of 94.9% (56/59) in the group combined with vitamin K antagonist anticoagulants. Compliance The diet rate in the anticoagulant group reached 91.5%. The rate of follow-up examinations on schedule is approximately two-thirds of patients (60.6%). Parents had good treatment compliance knowledge of 89%, and 11% had average knowledge. Some factors related to compliance include parents’ occupation, knowledge about compliance, severe illness and drug class. Conclusions: The medication compliance rate is quite high and parent compliance is higher in the group with severe illness.